The Existence of Benang Stokel Waterfall Tourism to Community Income - Desi Suryati -; Baiq Salkiah (Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar, 2020)
The tourism sector is a sector that has the potential to be developed, especially in West Nusa Tenggara. So the program of developing and utilizing the resources and potential of regional tourism is expected to contribute to economic development, especially for the income of the surrounding community. Central Lombok is one of the districts that have the potential to develop its tourism sector. One of the famous tourist destinations in Central Lombok district is the Benang Stokel Waterfall Tour. The existence of this tour provides a multiplier effect, especially on the income of the people around the tourist attractions. The purpose of this study was to determine the influence of the existence of Benang Stokel Waterfall Tour on people's income. This type of descriptive research using a quantitative approach, the number of samples of 30 people based on the determination of the sample by purposive sampling. The data source is the primary data equipped with secondary data. The data collection method used a questionnaire, namely a closed questionnaire, observation, and documentation, data analysis using statistical tests and statistical analysis. The results of statistical tests for the t value of 2.217 is greater than the t table value of 2.045 at a significant level of 5% or 2.217> 2.045. This shows that Benang Stokel Waterfall Tourism has an effect on people's income in Central Lombok. The existence of Benang Stokel Waterfall Tourism provides business opportunities for the community. Job opportunities that exist in the vicinity of tourist spots such as motorcycle taxi drivers, traders, and parking attendants with a mindseat that are formed are mindset guides, meaning that every ojek driver, trader, and parking attendant job has the ability to become a guide as well when taking tourists to their destination. This contributes to additional income for workers around tourist attractions. Apart from contributing to the surrounding community, Benang Stokel Waterfall Tourism also contributes to the regional income of Central Lombok Regency from the tourism sector. Keywords: Income; Society; Waterfall Tour.